An Interpretation of the Tragic Sense in F. Nietzsche’s Philosophy - Polovikaitė., Aušra (Problemos, 2002)
The article deals with our response to tragic drama as a problem in the philosophy of art. Why do we enjoy the dramatic portrayal of vice, deceit, human corruption, and death? Nietzsche’s writings on tragedy are primarily devoted to deciphering this classic problem. The early Greek drama made accessible through music to the audience-worshippers the Dionysian as an ecstatic and mystic direct connection with cosmic Nature (the Oneness), in which the individual will was obliterated. T he loss of the self in Nature produces the tragic joy. For the later Nietzsche, the relation between appearance and the Oneness is replaced by the relation between fictitious unities (values, forms, Jaws) and the chaotic multiplicity of forces which constitute the Will to Power.